UMP and Haro Sports working together in motor sports vehicle manufacturing - UMP, PNC (2019)
Universiti Malaysia Pahang (UMP) is set to be the first institute of higher learning in Malaysia to have the know-how in manufacturing motor sports vehicle and become the main manufacturer for the Formula Comet. The university signed a Memorandum of Understanding (MoU) with Haro Sports and Entertainment Sdn. Bhd. recently that would pave the way for collaborations in automotive engineering and exploring the possibilities that would help expand the motor and racing industry.